Assessing Bacterial Communities in Bulk Soil and Rhizosphere Associated with NPK Fertilizer in Oil Palm Seedlings via Amplicon Sequencing - bin Radzali, Mohamad Khairil; Amalia Mohd Hashim; Ho Li Sim; Joyce Ding Yoon Mei; Julia Ibrahim; Miratul Hada Mohd Ali; Mohd Termizi Yusof; Noor Azizah Musa; Nuha Hassim; Wan Zuhainis Saad (Malaysian Journal of Science, 2025)
Malaysia's palm oil industry relies heavily on chemical fertilizers, leading to significant environmental concerns such as nutrient loss and declining biodiversity. This study aims to evaluate the impact of post-fertilizer application on bacterial communities in soil, particularly focusing on bulk soil and rhizosphere. Through amplicon sequencing, we investigated the response of bacterial diversity to unfertilized and NPK-fertilized soil treatments. Fertilizer application increased soil phosphorus, potassium, and magnesium levels, enhancing seedlings’ growth but reducing bacterial diversity, particularly sensitive groups such as Acidobacteria and Verrucomicrobia. Candidatus Solibacter and Acidothermus were consistent biomarkers for unfertilized soil, while Mizugakiibacter and Castellaniella were for fertilized treatment. For the inferred bacterial community functions, the unfertilized bulk soil demonstrated enhanced function related to carbohydrate metabolism, and the unfertilized rhizosphere exhibited functions related to energy metabolism, stress tolerance, bioremediation, and plant defense. During fertilized treatment, functions related to secondary metabolites were enriched in the bulk soil, and bacterial colonization functions were enriched in both compartments. For network analysis, the fertilizer application reduced bacterial network interactions and complexity. Environmental drivers, namely, pH and soil total phosphorus (TP), influenced the bacterial biomarkers' abundance in the bulk soil and rhizosphere. These findings demonstrate the need to optimize chemical fertilizer applications and identify beneficial bacterial taxa to foster sustainable agricultural practices in the palm oil industry.